Using clinical indicators in emergency medicine: documenting performance improvements to justify increased resource allocation. Issue 5 (1st September 1999) - Rogers, I R; Evans, L; Jelinek, G A; Jacobs, I; Inkpen, C; Mountain, D
Abstract : OBJECTIVES: To demonstrate how emergency department triage scale and thrombolysis indicator data can be used to document the impact of a substantial increase in resource allocation. METHODS: Descriptive study in an emergency department of an adult tertiary hospital in Perth, Australia during similar periods of the year both before and after a substantial increase in emergency department staff, equipment, and system resources. The study group comprised a total of 11, 048 emergency department attendances and all cases of emergency department initiated thrombolysis or acute angioplasty. Outcome was measured using numbers seen and percentage seen within indicator threshold time together with admission rates in each of the five triage categories as well as by using time from presentation to initiation of reperfusion treatment in acute myocardial infarction. RESULTS: The proportion of patients seen within the prescribed indicator time increased by 16.4% (95% confidence interval 14.4% to 18.2%). The increase was most pronounced in triage category 2 (32.7%). Median time to thrombolysis fell by 30 minutes to 37 minutes (p = 0.0002). CONCLUSIONS: Use of the Australasian national triage scale and time to thrombolysis clinical indicator data allows a quantitative assessment of the impact of increased emergency department resource allocation.